2015
DOI: 10.1111/lasr.12164
|View full text |Cite
|
Sign up to set email alerts
|

Sentencing and State-Level Racial and Ethnic Contexts

Abstract: Sentencing studies have incorporated social context in studying sentencing decisions, but to date the bulk of prior work has focused almost exclusively on county context. An unresolved question is whether there also may be state‐level effects on sentencing. Drawing from the minority threat perspective, we examine (1) whether state‐level racial and ethnic contexts affect sentencing, (2) whether this effect amplifies the effect of county‐level racial and ethnic contexts on sentencing, and (3) whether the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 73 publications
0
40
1
Order By: Relevance
“…We then collected data on Hukou registration ( huji suozaidi ) of each criminal defendant by consulting with the Bureau of Public Security, the administrative unit responsible for population administration in China. In addition, as discussed earlier, since a substantial body of sentencing scholarship has shown that city‐level characteristics may have a contextual impact on sentencing outcomes (Wang and Mears ; Ulmer and Johnson 2004), we collected data about city‐level characteristics from the China City Statistical Yearbook of 2012 . Taken together, the data set used for our final analysis takes on a multilevel structure—in which criminal cases (level 1) are nested in urban jurisdictions (level 2)—and includes 1,050 criminal cases in 25 cities across China.…”
Section: Methodsmentioning
confidence: 99%
“…We then collected data on Hukou registration ( huji suozaidi ) of each criminal defendant by consulting with the Bureau of Public Security, the administrative unit responsible for population administration in China. In addition, as discussed earlier, since a substantial body of sentencing scholarship has shown that city‐level characteristics may have a contextual impact on sentencing outcomes (Wang and Mears ; Ulmer and Johnson 2004), we collected data about city‐level characteristics from the China City Statistical Yearbook of 2012 . Taken together, the data set used for our final analysis takes on a multilevel structure—in which criminal cases (level 1) are nested in urban jurisdictions (level 2)—and includes 1,050 criminal cases in 25 cities across China.…”
Section: Methodsmentioning
confidence: 99%
“…Conservative counties should punish defendants more severely if district attorneys and judges act in accordance with their voters (Chen, 2008). Like other studies that seek to measure political climate at the county level, conservatism is measured by the percentage of Republican voters (Wang & Mears, 2015;Weidner & Frase, 2003;Weidner et al, 2005).…”
Section: Political and Legal Climatementioning
confidence: 99%
“…Studies indicate that minority groups in various societies tend to receive harsher sentences than the majority group. For instance, in the United States, black defendants often receive harsher sentences for similar offenses than do white defendants (see, e.g., Ekstrand et al 1990;King et al 2010;MacDonald & Donnelly 2017;Petersilla 1983;Quereshi & King 1998;Spohn & DeLone 2000;Steffensmeier et al 1998;Ulmer et al 2016;Wang & Mears 2015). 1 Studies in Israel show a similar discrepancy in the sentencing of Jews, who make up Israel's majority, and Israeli-Arabs, a minority group comprising about 21 percent of the population (Cohen et al 1985;Hassin & Kremnitzer 1988;Rahav et al 2016;Rattner & Fishman 1998).…”
Section: Introductionmentioning
confidence: 99%